Evidence for STIM1- and Orai1-dependent store-operated calcium influx through I(CRAC) in vascular smooth muscle cells: role in proliferation and migration - Potier, Marie (The Federation of American Societies for Experimental Biology, 2009)
The identity of store-operated calcium (Ca(2+)) entry (SOCE) channels in vascular smooth muscle cells (VSMCs) remains a highly contentious issue. Whereas previous studies have suggested that SOCE in VSMCs is mediated by the nonselective transient receptor potential canonical (TRPC) 1 protein, the identification of STIM1 and Orai1 as essential components of I(CRAC), a highly Ca(2+)-selective SOCE current in leukocytes, has challenged that view. Here we show that cultured proliferative migratory VSMCs isolated from rat aorta (called “synthetic”) display SOCE with classic features, namely inhibition by 2-aminoethoxydiphenyl borate, ML-9, and low concentrations of lanthanides. On store depletion, synthetic VSMCs and A7r5 cells display currents with characteristics of I(CRAC). Protein knockdown of either STIM1 or Orai1 in synthetic VSMCs greatly reduced SOCE, whereas Orai2, Orai3, TRPC1, TRPC4, and TRPC6 knockdown had no effect. Orai1 knockdown reduced I(CRAC) in synthetic VSMCs and A7r5 cells. Synthetic VSMCs showed up-regulated STIM1/Orai1 proteins and SOCE compared with quiescent freshly isolated VSMC. Knockdown of STIM1 and Orai1 inhibited synthetic VSMC proliferation and migration, whereas STIM2, Orai2, and Orai3 knockdown had no effect. To our knowledge, these results are the first to show I(CRAC) in VSMCs and resolve a long-standing controversy by identifying CRAC as the elusive VSMC SOCE channel important for proliferation and migration.—Potier, M., Gonzalez, J. C., Motiani, R. K., Abdullaev, I. F., Bisaillon, J. M., Singer, H. A., and Trebak, M. Evidence for STIM1- and Orai1-dependent store-operated calcium influx through I(CRAC) in vascular smooth muscle cells: role in proliferation and migration.